The big picture with Ricky Carandang. - Carandang, Ricky ([s.n.], 2010)
Five part series on the Philippine economy. Experts in the field were invited to share thoughts on the current economic issues, what was done in the past to address the issues and what current administration can do to solve these issues. These Big Picture interviews were aired on ABS-CBN News Channel (ANC).